2023
DOI: 10.1128/spectrum.03508-22
|View full text |Cite
|
Sign up to set email alerts
|

Urease of Aspergillus fumigatus Is Required for Survival in Macrophages and Virulence

Abstract: The development of antifungal drugs is an urgent task, but it has proven to be difficult due to many similarities between fungal and animal cells. Here, we characterized the urease system in A. fumigatus , which depends on nickel for activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Urease is critical for the growth of A. fumigatus, urea being the sole nitrogen source of this fungus. In studies carried out by Xiong et al [92], there was an increase in the transcriptional level of urease mRNA after A. fumigatus was grown in urea media. It was demonstrated that a urease mutation in S. cerevisiae led to an increased expression of NCR-regulated genes under conditions of repression [93][94][95].…”
Section: Discussionmentioning
confidence: 96%
“…Urease is critical for the growth of A. fumigatus, urea being the sole nitrogen source of this fungus. In studies carried out by Xiong et al [92], there was an increase in the transcriptional level of urease mRNA after A. fumigatus was grown in urea media. It was demonstrated that a urease mutation in S. cerevisiae led to an increased expression of NCR-regulated genes under conditions of repression [93][94][95].…”
Section: Discussionmentioning
confidence: 96%
“…The transcript and protein levels are elevated on urea media. The urease deficient mutant displays attenuated virulence, and its spores are more susceptible to macrophage-mediated killing [28] .We can hypothesize that elevated blood urea nitrogen levels may facilitate the growth of Aspergillus spores in the body and prevent them from being phagocytized by macrophages, leading to IPA. However, this requires further experimentation to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that most of Nitrospira genomes lack ureE that serves as a bridge to acquire nickel from hydrogenase maturation factor HypA, which is subsequently donated to UreG. HypA is a metallochaperone and selectively delivers the nickel to the active site ( Xiong et al, 2023 ). The absence of ureE may result in low urease activity in NOB ( Carter et al, 2009 ; Fujitani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%